2009
DOI: 10.1007/978-3-642-02348-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Well-Definedness of Streams by Termination

Abstract: Abstract. Streams are infinite sequences over a given data type. A stream specification is a set of equations intended to define a stream. We propose a transformation from such a stream specification to a TRS in such a way that termination of the resulting TRS implies that the stream specification admits a unique solution. As a consequence, proving such well-definedness of several interesting stream specifications can be done fully automatically using present powerful tools for proving TRS termination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 11 publications
(24 reference statements)
0
25
1
Order By: Relevance
“…In [52,53], Zantema defines 'proper' stream specifications. These are similar to shallow tree specifications, but differ in two aspects:…”
Section: Comparison Of Input Formatsmentioning
confidence: 99%
“…In [52,53], Zantema defines 'proper' stream specifications. These are similar to shallow tree specifications, but differ in two aspects:…”
Section: Comparison Of Input Formatsmentioning
confidence: 99%
“…From [5] we recall the two variants of the main theorem. In [5] it is shown by an example that this distinction is essential: uniqueness of stream functions does not hold if the stream specification is data dependent, that is, left hand sides contain symbols 0 and 1.…”
Section: Definitionmentioning
confidence: 99%
“…In [5] it is shown by an example that this distinction is essential: uniqueness of stream functions does not hold if the stream specification is data dependent, that is, left hand sides contain symbols 0 and 1. Moreover, in [5] it has been shown that the technique is not complete: some fix-point specifications are well-defined while the observational variant is non-terminating.…”
Section: Definitionmentioning
confidence: 99%
See 2 more Smart Citations